Design of RIVAL (Cari Travel Malang) Application as One Stop App Solution for Travel Reservation in Malang - Novita Rosyida; Agung Dwi Saputra (Journal of Indonesian Tourism and Development Studies, 2020)
Reservations can be interpreted as order transaction for place, ticket, or goods between business owners or service providers with consumers. In travel reservation, especially in Malang, people do some travel reservations manually. They reserve the travel by phone to the travel customer service or came to the travel office. Based on the problem, the author made an application called RIVAL (Cari Travel Malang) as one-stop app solution for travel reservation in Malang that runs on mobile platform with android operating system. In this design phase, application is still local or runs on the developer local server and runs online for application testing to several people. With this application it is expected that travel reservation that are initially carried out manually by coming to service provider, now it can be done anywhere. The results of the implementation and testing were given to eight respondents with several different versions of the Android operating system namely Android Lollipop, Marshmallow, Oreo, and Pie. It was found that the application runs well without any UI constraints or main functions in the application with additional data response obtained from the test questionnaire form that the application is easy to understand from the user interface, provided information, and easy to use. With this application, it is expected travel reservation in Malang can be done easily and efficiently.Keywords: Mobile application, reservation, travel application.